Voltage support strategy for PV inverter to enhance dynamic voltage stability of islanded microgrid. (October 2020) - Afrin, Nadia; Yang, Fuwen; Lu, Junwei
Highlights: Coordinated active and reactive power control as voltage support is proposed. Margin residue of the inverter, as well as voltage level, is considered. Effectiveness of the proposed strategy in comparison with others is investigated. Proposed strategy can enhance dynamic voltage stability of studied microgrid. Abstract: This paper presents a voltage support (VS) strategy for grid feeding photo-voltaic (PV) inverter with new coordination between the active and reactive current injection to improve the dynamic voltage stability (DVS) of islanded microgrid (MG). In order to limit the supplied current from the inverter within the maximum allowable current, a new variable, margin residue, is defined in the proposed VS strategy. Moreover, the coordination between active and reactive current is segmented by taking into account the voltage level as well as the margin residue. The DVS of two islanded MGs is investigated to present the effectiveness of the proposed strategy in enhancing it. From the illustrated results, it is shown that the new strategy can provide an improved DVS in comparison with other strategies under similar network conditions.